I Inovasi Tas Wanita dengan Media Keramik - I Made Sujana; I Ketut Muka Pendet; I Nyoman Laba (Pusat Penerbitan LP2MPP ISI Denpasar, 2021)
Women in carrying out activities are usually equipped with the use of bag products. The use of bags by women as complementary goods is combined with clothing to harmonize style and improve self-image in society. This phenomenon has inspired creators to create innovative women's bags with ceramic media inspired by the Rejang Asak Da nce crown as a source of creation ideas. The purpose of this creation: 1. How is the process of creating women's bags with ceramic media ?; 2. What are the results of the innovation of women's bags with ceramic media ? The stages of creation are the first to do exploration with observation, interviews, and documentation, the second stage is the design of the bag creation work in the form of rough sketches or manual sketches, and the third is the embodiment of the design. The results of the creation in the form of a Shoulder Bag, Sling Bag and Hand Bag.